Information and knowledge management as the key to success for social activism - Sanz-Martos, Sandra (Anuario ThinkEPI, 2014)
One of the many effects of the economic crisis is that public and private organizations are cutting back on Knowledge Management initiatives. This might also be interpreted as a sign of organizational skepticism towards their true value and/ or the benefits they entail. However, in social activism platforms these benefits are clearly perceived, and it could be argued that the management of information and knowledge has proved to be the key to their success.